Inclusive targeting: a multistep validation of the poverty probability index for the identification of low-income students in developing countries - Cristina Nataly Cadena-Palacios; Ismenia Araujo; Rocío Alejandra Duque; Andrés Benítez Soto (Cogent Social Sciences)
The study of effective targeting mechanisms for identifying households or individuals eligible for poverty reduction, development, and social protection programs is a pressing issue for practitioners and civil society. The paper presents a validation strategy that practitioners could use to identify potential beneficiaries of poverty reduction, inclusion, and institutional programs, especially in the resource-constrained settings prevalent in developing countries. The approach integrates a multistep process to ensure internal and external validity when using the Poverty Probability Index to identify students living in poor households. The results strongly support the internal and external validity of the proposed strategy’s targeting mechanism. The combination of the Poverty Probability Index and z-scores allows for identifying vulnerable students, offering an opportunity for a low-cost and time-efficient poverty analysis that practitioners could use in diverse settings. This will enable the implementation of unbiased scholarship programs for students of higher education institutions in developing economies.